Clinical evolution and medical resource utilization in adult patients with respiratory syncytial virus infection at a community hospital in Argentina - Agustin Bengolea; Juan I. Ruiz; Celina G. Vega; Matias Manzotti; Nadia Zuccarino; Lucila Rey-Ares (PLoS ONE, 2025)
Objective To describe the hospital medical resources used in adults hospitalized with respiratory syncytial virus infection and to evaluate the association of comorbidities with resource utilization and clinical outcomes. Design A retrospective cohort study was conducted using the electronic healthcare database of Hospital Alemán, Buenos Aires, Argentina. It included hospitalized patients aged 18 years or older who had a positive test for respiratory syncytial virus between September 2010 and December 2023. Data were analyzed using standard statistical methods following STROBE guidelines. Results Among 72 hospitalized adults with confirmed respiratory syncytial virus infection, the mean length of hospital stay was 12.18 days (SD 12.91), and 27 (37.5%) patients required intensive care unit admission. Healthcare resource utilization was substantial, with 26% needing non-invasive ventilation and 11% requiring mechanical ventilation. Antibiotics (75%) and corticosteroids (68.05%) were commonly used, likely reflecting the severity of clinical presentation or the potential for bacterial coinfection. Cardiovascular comorbidities were significantly associated with severe disease outcomes and intensive care unit admission (OR 3.53, 95% CI: 1.00–12.54). Comparative analysis with 226 influenza patients showed respiratory syncytial virus patients had longer hospital stays and higher intensive care unit admission rates. Conclusions Respiratory syncytial virus infection in adults resulted in substantial medical resource utilization and significant intensive care unit admission and ventilation support requirements. Cardiovascular comorbidities might be associated with increased severity and intensive care unit admissions. The high rate of antibiotic use is noteworthy and warrants further investigation to understand prescribing patterns and optimize antimicrobial stewardship. Compared to influenza, respiratory syncytial virus appears to be associated with longer hospital stays and higher intensive care unit admissions, highlighting the need for tailored management strategies for respiratory syncytial virus in adult populations. Further research should focus on optimizing treatment protocols and preventive measures for respiratory syncytial virus.